2018
DOI: 10.1007/s40858-018-0254-9
|View full text |Cite
|
Sign up to set email alerts
|

Fitness costs associated with G461S mutants of Monilinia fructicola could favor the management of tebuconazole resistance in Brazil

Abstract: In this study, we investigated the sensitivity components of demethylation fungicide inhibitors (DMI-tebuconazole) for two different sensitivity genotypes of Monilinia fructicola (G461S mutants and wild-type isolates). These components included the fungicide resistance stability and fitness studied over the course of nine and five successive transfers in vitro and ex vivo, respectively, in the absence of fungicide. The results showed no effect of successive transfers on tebuconazole sensitivity of isolates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Typically, pathogens with some of the mechanisms of resistance to DMI fungicides present low fitness after selective pressure reduction (Cox et al , ; Egüen et al , ). In Brazil, Lichtemberg et al () clearly demonstrated the fitness and competitiveness disadvantage of isolates with the G461S mutation, which confers resistance to DMI fungicides, compared to wildtype isolates. This evidence suggests that population sensitivity can be restored after discontinuous use of DMIs in orchards with a high frequency of M. fructicola resistant to these fungicides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, pathogens with some of the mechanisms of resistance to DMI fungicides present low fitness after selective pressure reduction (Cox et al , ; Egüen et al , ). In Brazil, Lichtemberg et al () clearly demonstrated the fitness and competitiveness disadvantage of isolates with the G461S mutation, which confers resistance to DMI fungicides, compared to wildtype isolates. This evidence suggests that population sensitivity can be restored after discontinuous use of DMIs in orchards with a high frequency of M. fructicola resistant to these fungicides.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, this change in sensitivity was attributed to the high fitness cost of resistance. Additionally, several studies have shown that reduced sensitivity to DMI fungicides has a fitness cost on populations of M. fructicola , such as lower vegetative, reproductive and competitive capacity and reduced ability to cause disease in comparison to sensitive isolates (Cox et al , ; Chen et al , ; Zhu et al , ; Lichtemberg et al , ). These studies suggest that resistance could be managed by reducing the number of applications or even by discontinuing DMI applications for some crop years.…”
Section: Introductionmentioning
confidence: 99%
“…The cell membrane relative permeability rate for tebuconazole-sensitive or resistant isolates was evaluated according to the described method [ 25 ] with some modifications. The activated mycelia were respectively inserted into the PDB medium, and shaken (120 r/min) for 3 d; then, the fresh mycelium was collected, and later washed with double-distilled sterile water and vacuum filtered.…”
Section: Methodsmentioning
confidence: 99%
“…In commercial areas of stone fruit production, considerable use of synthetic fungicides like dicarboximides (DCFs), methyl benzimidazoles carbamates (MBCs), demethylation inhibitors (DMIs), quinone outside inhibitors (QoIs) and succinate dehydrogenase inhibitors (SDHIs) results in the induction of resistance in Monilinia spp. For example, isolates of M. fructicola showing resistance against MBC fungicide benomyl (Chen et al, 2014) and to DMI fungicides are reported from the USA (Chen et al, 2013) and by other regions such as Brazil (May-De Mio et al, 2011;Lichtemberg et al, 2019), Greece (Malandrakis et al, 2012), Spain (Egüen et al, 2015), and Serbia (Hrustić et al, 2018). Overexpression or mutations of the 14α-demethylasegene (MfCYP51) is responsible for resistance against DMI fungicides.…”
Section: Chemical Controlmentioning
confidence: 99%